Azelnidipine nanoparticles break calcium homeostasis and induce severe ER stress combined with medroxyprogesterone acetate for endometrial cancer therapy. (December 2022) - Huang, Ting; Zhou, Jingyi; Zhang, Lingpu; Yang, Xiao; Cheng, Yuan; Yin, Shenyi; Wang, Jiaqi; Shen, Boqiang; Feng, Xuan; Li, Xingchen; Dong, Yangyang; Xiao, Haihua; et al.
Abstract: Calcium homeostasis plays a crucial role in many cellular processes. The disruption of calcium homeostasis triggers endoplasmic reticulum (ER) stress and contributes to cell death, thus representing a potential target for cancer therapy. Calcium channel blockers (CCBs) are the first-line calcium ion modulators for hypertension but with anti-tumor activities. However, their effects on the cardiovascular system and the poor water solubility hampered their widespread use as anticancer drugs. Herein, we screened out Azelnidipine (AZL) of 19 FDA-approved CCBs, and found AZL had the best tumor inhibitory effect on endometrial cancer (EC) cells. Subsequently, liposomes are adopted to encapsulate AZL to form nanoparticles (NP@AZL) for drug delivery. NP@AZL showed better inhibitory effects on four EC cell lines and advanced patient-derived cells (PDCs) than AZL alone in vitro . Inside a cancer model of EC-bearing mice, NP@AZL was able to accumulate in the tumor, and combine with medroxyprogesterone acetate (MPA) to significantly inhibit tumor growth. Mechanistic study by transcriptome revealed that NP@AZL combined with MPA resulted in severe ER stress, and upregulation of pro-apoptotic genes, ultimately inhibiting DNA replication to promote cell death. Therefore, the strategy of disrupting calcium homeostasis and activating severe ER stress through combination therapy may serve as a paradigm for future EC treatment. Graphical Abstract: ga1 Highlights: High calcium levels are associated with EC progression. AZL was screened out of 19 FDA-approved CCBs for its outstanding anticancer effects in EC cells. NP@AZL was prepared to functionalize the liposomes for targeted delivery. NP@AZL triggered ER stress, activated CHOP-TRIB3 pathway and promoted cell apoptosis. NP@AZL synergized with MPA resulted in severe ER stress and promoted EC cell death.